Nonlinear dynamic response and vibration of imperfect shear deformable functionally graded plates subjected to blast and thermal loads. Issue 4 (12th March 2017) - Dinh Duc, Nguyen; Tuan, Ngo Duc; Tran, Phuong; Quan, Tran Quoc
ABSTRACT: Based on Reddy's higher-order shear deformation plate theory, this article presents an analysis of the nonlinear dynamic response and vibration of imperfect functionally graded material (FGM) thick plates subjected to blast and thermal loads resting on elastic foundations. The material properties are assumed to be temperature-dependent and graded in the thickness direction according to a simple power-law distribution in terms of the volume fractions of the constituents. Numerical results for the dynamic response and vibration of the FGM plates with two cases of boundary conditions are obtained by the Galerkin method and fourth-order Runge–Kutta method. The results show the effects of geometrical parameters, material properties, imperfections, temperature increment, elastic foundations, and boundary conditions on the nonlinear dynamic response and vibration of FGM plates.